Difference Of Community Assessment and Perception Marketing Mix (7P) on Service Satisfaction in UNISMA Hospital Malang - Ratna Sari, Dwi; Widyaningrum, Kurnia; Wahyu Sarwiyata, Tri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2023)
Globalization has a big impact on the development of the business world and opportunities for institutions engaged in services. Hospitals are required to find new marketing ideas/strategies in maintaining their existence and improving the quality of services for the creation of patient satisfaction. The lack of promotion of superior hospital products (50%) and the low results of patient satisfaction surveys for services (30%) indicate the need to improve aspects of the marketing mix at Unisma Hospital in Malang. This study aims to analyze public perceptions of the marketing mix (7P) in service satisfaction at Unisma Malang Hospital. This study is in the form of a survey (cross sectional study approach) with 85 respondents selected using the accidental sampling method. The data collection method was carried out through interviews and using a service satisfaction questionnaire containing a marketing mix (7P) component. The results showed that of the 7 aspects of marketing mix there were 2 dominant aspects and there was a need for improvement, namely the promotion aspect where 41 chose the lack of activities made by RSI Unisma as the promotion of RSI Unisma and the process aspect where as many as 54 chose the lack of speed and accuracy of the service. Therefore, based on these problems, it is necessary to improve the hospital marketing strategy and improve the quality of service. The solution to this problem is to promote activities that are under the auspices of the Nahdlatul Ulama as an effort to promote and review services, processes and procedures. Keywords: Perception, Marketing Mix, Patient Satisfaction